2006
DOI: 10.3892/or.16.6.1181
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of a water-soluble extract from the culture medium of Ganoderma lucidum (Rei-shi) mycelia on the development of pulmonary adenocarcinoma induced by N-nitrosobis (2-hydroxypropyl) amine in Wistar rats

Abstract: Abstract.A water-soluble extract from the culture medium of Ganoderma lucidum (Rei-shi) mycelia (MAK) has been shown to exert a potent chemopreventive effect. The present study was designed to investigate the effects of dietary MAK supplementation on the development of lung tumors initiated by N-nitrosobis (2-hydroxypropyl) amine (BHP) in male Slc:Wistar rats. A total of 77 animals, 6 weeks of age, were divided into 5 groups and given BHP (2,000 ppm) in their drinking water for 10 weeks. The normal controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In general, high molecular weight contributes to anti-cancerous activity of plant polysaccharides, whereas reports also suggested that even low MW equally influence the anti-cancerous activities ( Kashimoto et al, 2006 ). One study revealed that partially cellulose digested Aloe polysaccharide fractions within the size of 5–400 kDa had the most potent anti-cancerous activity, depicting the importance of size of polysaccharide for its biological activity ( Im et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, high molecular weight contributes to anti-cancerous activity of plant polysaccharides, whereas reports also suggested that even low MW equally influence the anti-cancerous activities ( Kashimoto et al, 2006 ). One study revealed that partially cellulose digested Aloe polysaccharide fractions within the size of 5–400 kDa had the most potent anti-cancerous activity, depicting the importance of size of polysaccharide for its biological activity ( Im et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fruit bodies, cultured mycelia and spores of Ganoderma lucidum were reported to be effective in the treatment of chronic hepatopathy, hypertension, hyperglycemia and cancer (Hong et al, 2004;Sliva, 2006;Liu et al, 2009). Many reports showed Ganoderma lucidum to possess antiproliferative effects on many cancers, such as acute myelogenous leukemia, lung cancer, breast cancer, and prostate cancer (Chui et al, 2006;Kashimoto et al, 2006;Thyagarajan et al, 2006;Xie et al, 2006;Yue et al, 2006). It was also demonstrated that Ganoderma lucidum extract has a profound activity against leukemia, lymphoma and multiple myeloma cells and may be a novel adjunctive therapy for the treatment of hematologic malignancies (Müller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma lucidum ( G. lucidum , Reishi or Ling-Zhi) has been used in traditional Chinese medicine as an anti-tumor medication or as an immuno-modulator. Many reports showed Reishi extracts to possess anti-proliferative effects on many cancers, such as acute myelogenous leukemia [ 1 ], lung cancer [ 2 ], breast cancer [ 3 ], colorectal cancer [ 4 ], bladder cancer [ 5 ] and prostate cancer [ 6 , 7 ]. A fucose-containing polysaccharide fraction (F3), isolated from the water-soluble Reishi extract, is able to stimulate spleen cell proliferation and cytokine expression [ 8 - 11 ].…”
Section: Introductionmentioning
confidence: 99%